Pembuatan Bioetanol Dari Limbah Padat Sagu Menggunakan Enzim Selulase Dan Yeast Saccharomyces Cerevisiae Dengan Proses Simultaneous Sacharificatian and Fermentation (SSF) Dengan Variasi Konsentrasi Substrat Dan Volume Inokulum - Yolanda Amalia; Sri Rezeki Muria; Chairul Chairul (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Bioethanol is a renewable alternative energy source that can be used as an alternative fuel . One material that has potential as bioethanol feedstock is a solid waste sago , which is the sago industry solid waste that has not been optimally dimanfatkan . The content of cellulose in the solid waste can be converted into bioethanol sago by using simultaneous saccharification and fermentation ( SFS ) process . This research aims to find out how much solid waste can be converted into bioethanol sago with variation of substrate concentration and volume of inoculum , and to determine the influence of substrate concentration and volume of inoculum at the SFS . The variation of this research are the substrate concentration 40 g , 60 g and 80 g and volume variations of inoculum 10 % and 12.5 % at the fermentation time for 96 hours at pH optimum of 5. The process of saccharification uses cellulase enzymes and Saccharomyces cervisiae yeast for the fermentation process. The samples were conducted by using alcoholmeter . The results of this research showed that the highest ethanol which obtained at the SFS process using cellulase enzyme and Saccharomyces cervisiae yeast reached 8 % for 72 hours fermentation time, the variation of the substrate concentration 80 g and 12.5 % inoculum volume  Keywords : ethanol , cellulase enzymes , fermentation , sago , Saccharomyces cerevisiae